UV-Visible Spectroscopic Analysis of Influence of Trace Element Ions on Albendazole - UTHRA*, D.; ANITA, B.; SURIYA, B. (Asian Journal of Chemistry, 2009)
Prersent work aims to employ UV-Visible spectral analysis of ananthelmentic drug albendazole. This drug falls under the category ofWHO's model list of essential drugs for the eradication of helminthiasis.The interaction of this drug with certain ions like sodium, calcium andpotassium which are present in blood as trace elements has been studiedwith the aid of UV-Visible spectroscopy as a tool.